How to approach childhood obesity. Issue 2 (February 2022) - Patterson, Rosemarie; Sornalingam, Sangeetha; Hannah, Romanie; Cooper, Max
Childhood obesity has a rising prevalence and is associated with significant morbidity, social and psychological consequences. In England, 21% of children aged between 10 and 11 are obese, with the highest rates being among children from lower socioeconomic groups. Primary care is responsible for managing most children who are overweight or obese. Consultations should generate positive conversations about childhood obesity and rule out underlying conditions and co-morbidities. Families may need support to recognise contributing factors and should be encouraged to identify simple, achievable strategies to promote healthier choices. Follow-up is essential, and families should be referred on to appropriate services for ongoing support.